A study on the impact of sidewalk services on pedestrian functions and user perception of Jalan A. P Pettarani Makassar - Marlinda Wanti; Lambang Basri Said; St. Fauziah Badaron (Jurnal Scientia, 2024)
The increasing level of urbanization often corresponds with heightened levels of activity and events within a city. This phenomenon is exemplified in the bustling environment of Jalan A.P Pettarani, Makassar, where the proliferation of activities has led to a dense concentration of community engagement along its roads. Despite this vibrancy, the development of sidewalks on Jalan A.P Pettarani has catalyzed the influx of active pedestrians. However, the functionality of these sidewalks has been compromised, lacking essential facilities that would otherwise enhance pedestrian comfort. This study aims to meticulously analyze the effectiveness of the current pedestrian pathways along Jalan A.P Pettarani, Makassar, alongside evaluating public perceptions regarding their functionality. Employing a descriptive qualitative methodology, the research integrates the utilization of SPSS software to assess pedestrian functionality based on the specifications outlined in PUPR No. 2/SE/M/2018, while also delving into public opinions on pedestrian functions. The findings underscore a pressing concern, indicating that the existing condition of the pedestrian pathways along Jalan A.P Pettarani only achieves a meager 41.6% effectiveness rating, falling short of the standards set by Research and Development (1991) for functionality. Furthermore, the analysis of public perceptions reveals insightful perspectives; infrastructure emerges as the most influential variable, commanding 48.7% of respondents' concerns, followed by safety (36.9%), health (17.4%), and environment (12.2%). Accessibility, though crucial, garners the least attention, with a mere 4.7% focus from respondents. Overall, this study sheds light on the urgent need for improvements in pedestrian infrastructure along Jalan A.P Pettarani, Makassar, highlighting the significant impact it holds on public perception and usability. Addressing these deficiencies is paramount in fostering a pedestrian-friendly environment conducive to the city's ongoing development and the well-being of its inhabitants.